The influence of referee bias on extra time in elite soccer matches - Lago-Peñas, C.; Gómez-López, M. (Perceptual and Motor Skills, 2016)
Referees have discretion over the addition of extra time at the end of the soccer game to compensate for lost time due to unusual stoppages. This study assesses if referees favor big teams by shortening close games where the big team is ahead and lengthening close games where the big team is behind. The sample comprises all 380 matches in the Spanish La Liga during the 2014-2015 season. The dependent variable was the extra time the referee decides to add to the second half. The independent variables were the score difference, opponent team's level of play, yellow cards, red cards, player substitutions, average attendance, and fouls committed. Linear regression analysis suggested that the greater the score difference between teams, the less extra time was added by the referee. However, in close games, referees tended to add more time for a higher level team when they were behind and add less time when they were ahead. Red cards and the number of fouls committed increased the extra time.